2019
DOI: 10.3389/fmicb.2019.02658
|View full text |Cite
|
Sign up to set email alerts
|

FolVps9, a Guanine Nucleotide Exchange Factor for FolVps21, Is Essential for Fungal Development and Pathogenicity in Fusarium oxysporum f. sp. lycopersici

Abstract: The soil-borne, asexual fungus Fusarium oxysporum f.sp. lycopersici (Fol) is the causal agent of tomato wilt disease. Autophagy plays a crucial role in the development and virulence of Fol. The Fol endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity. Rab GTPases and the regulators are highly conserved in regulating autophagy and endocytosis in most eukaryotes. Identification and characterization of additional Rab regulators in fungal pathogens should fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
(96 reference statements)
1
10
0
Order By: Relevance
“…Here, our data have shown that Vps9 domain, rather than CUE domain, in FgVps9 regulates the endosomal localization and physiological functions of the entire protein in F. graminearum. This result is consistent with that observed in Fol (Li et al, 2019), indicating that the function of Vps9 domain is pleiotropic in fungi. We also found that the two GEF activity sites in the FgVps9 domain play an essential role in F. graminearum.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Here, our data have shown that Vps9 domain, rather than CUE domain, in FgVps9 regulates the endosomal localization and physiological functions of the entire protein in F. graminearum. This result is consistent with that observed in Fol (Li et al, 2019), indicating that the function of Vps9 domain is pleiotropic in fungi. We also found that the two GEF activity sites in the FgVps9 domain play an essential role in F. graminearum.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, FgVPS9 deletion mutant also shows reduced vegetative growth, endocytosis, virulence, and DON production, while autophagy is only partially blocked in Fgvps9 mutant with most autophagosomes labeled by GFP-ATG8 fused to vacuoles in liquid MM-N media. However, in P. oryzae and Fol, remarkably less fluorescence signals of GFP-ATG8 and few autophagosomes were examined in the vacuoles of the Povps9 and Folvps9 mutants when comparing with those of wild-type strains, suggesting that autophagy is seriously blocked in Povps9 and Folvps9 mutants (Zhu et al, 2018;Li et al, 2019). Collectively, these data indicated that, similar with PoVps9 and FolVps9, FgVps9 functions in both endocytosis and autophagy processes, which involved in fungal growth, virulence, and DON production; however, the role of FgVps9 on autophagy is not as important as its homologs in P. oryzae and Fol.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations